Control Divergence, Timeliness in Loss Recognition, and the Role of Auditor Specialization: Evidence from around the World - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2009)
This paper seeks to investigate how control-cash flow divergence of a firm's ultimate owner may affect the timeliness of accounting recognition of economic losses (TLR) relative to recognition of economic gains, and if engaging an audit industry specialist mitigates the reduced TLR arising from control divergence. Our results show that firms with greater divergence in control and cash flow rights are less timely in loss recognition (relative to gain recognition). We also find evidence that clients audited by industry specialists are associated with greater TLR. More important, we find that the negative association between control divergence and the TLR is moderated by the auditor industry specialization. The results are robust to controls for legal institutions, political economy, extralegal institutions, firm and industry characteristics, and the potential endogeneity between auditor choice and control divergence. Given that Bushman, Piotroski, and Smith (2006) provide evidence to suggest that TLR is a desirable attribute of accounting since it leads to significant positive economic consequences, the findings of our study suggest that hiring an audit industry specialist in the presence of control divergence can lead to positive economic consequences for the firm.